Effects of replacing inorganic trace minerals with organic trace minerals on the production performance, blood profiles, and antioxidant status of broiler breeders. (19th February 2019) - Wang, G; Liu, L J; Tao, W J; Xiao, Z P; Pei, X; Liu, B J; Wang, M Q; Lin, G; Ao, T Y
ABSTRACT: This study was conducted to investigate the effects of replacing inorganic trace minerals (ITMs) with organic trace minerals (OTMs) on the production performance, blood profile, and antioxidative status of broiler breeders. A total of 600 healthy broiler breeder hens, aged 40 wk, were randomly divided into 5 treatments with 4 replicates in each treatment, and fed for 10 wk. Experimental treatments were: (1) commercial levels of inorganic minerals (COM); (2) L-ITM (50% of the COM, except for Se); (3) VL-OTM (37.5% of the COM, except for Se); (4) L-OTM (equivalent to L-ITM); and (5) OTM (62.5% of the COM, except for Se). The laying rate was 9.56% higher, feed-to-egg ratio was 7.83% lower, and rate of qualified eggs was 18.33% higher ( P  < 0.05) for L-OTM compared to L-ITM despite equal mineral levels. The fertility with COM was significantly higher ( P < 0.05) than L-ITM, VL-OTM, or L-OTM treatments. OTM and COM treatments both had increased serum LH and P4 . The relatively higher mineral levels fed in COM and OTM treatments increased blood total protein ( P < 0.05). In addition, activities of serum GSH-Px, Mn-SOD, and T-SOD were higher ( P < 0.01), while malondialdehyde (MDA) content was lower ( P < 0.05), for COM and OTM birds as compared to L-ITM and VL-OTM. The serum T-SOD of L-OTM birds was significantly higher (9.81%; P < 0.01) than that of L-ITM birds. Higher ( P < 0.05) activities of liver GSH-Px and T-SOD, and lower MDA concentrations ( P < 0.01) were measured in the COM, L-OTM, and OTM treatments than the L-ITM treatment. Collectively, total replacement of high levels of ITMs by lower levels of OTMs in broiler breeder diets was beneficial for productive performance under the conditions of this study.